Effectiveness of Labor Cervical Examination Simulation in Medical Student Education. (October 2015) - Nitsche, Joshua F.; Shumard, Kristina M.; Fino, Nora F.; Denney, Jeffrey M.; Quinn, Kristen H.; Bailey, John C.; Jijon, Rubymel; Huang, Chenchen; Kesty, Kendra; Whitecar, Paul W.; Grandis, Arnold S.; Brost, Brian C.
Abstract : OBJECTIVE: To estimate whether simulation training improves medical students' cervical examination accuracy. BACKGROUND: The training paradigm for the labor cervical examination exposes patients to additional examinations, lacks a gold standard, and does not objectively assess trainee competence. To address these issues and optimize training, we assessed the effectiveness of cervical examination simulation in third-year medical students. METHODS: During the obstetrics and gynecology clerkship, a cohort study was performed in which third-year students were assigned to receive cervical examination simulation (n=50) or vaginal delivery simulation (n=48), with each group serving as a simulation-naive control for the other skill. As a final assessment, students performed 10 cervical examinations using task trainers. Exact accuracy and accuracy within 1 cm were compared between groups. Cumulative summation analyses were performed on the cervical examination group to assess competence and the average number of repetitions needed to achieve it. RESULTS: Cervical examination students were significantly more accurate (Mann-Whitney, P <.001) in assessing dilation (73% exact, 98% within 1 cm) and effacement (83% and 100%) than vaginal delivery students (dilation 52% and 82%, effacement 51% and 96%). In the cumulative summation analyses, 65–100% of students attained competence during the clerkship depending on the level of accuracy and cervical parameter assessed. On average, competence was achieved with 27–44 repetitions. CONCLUSION: Simulation training dramatically improved student accuracy in labor cervical examinations. Because not all students achieved competence, the cumulative summation analyses suggest that more than 100 repetitions would be needed if the goal was for the entire class of students to achieve competence. LEVEL OF EVIDENCE: II Abstract : Use of simulation training significantly improves medical student accuracy in the labor cervical examination and defines many key training parameters for this important skill.